Nanoindentation study of the interfacial zone between cellulose fiber and cement matrix in extruded composites - Teixeira, R. S.; Tonoli, G. H.D.; Santos, S. F. [UNESP]; Rayón, E.; Amigó, V.; Savastano, H.; Rocco Lahr, F. A. (Elsevier, 2018)
The present study shows the application of the nanoindentation technique to evaluate the properties of the cellulose fiber-cement matrix interfacial zone in composites prepared with an auger extruder. The degree of strength of the bond between fiber and matrix is recognized as important variable that influences macro-mechanical properties, such as modulus of rupture and toughness of cement based composites. The nanoindentation measurements showed the highest hardness and elastic modulus in the part inner of the cellulosic fiber after hydration process due to precipitation and re-precipitation of cement hydration products. These results indicate that mineralization of the cellulosic fibers can affect the stress distribution and interfacial bond strength in the cement based composite.
Keywords: Mechanical properties; Microstructure; Ordinary Portland cement; Transition zone; Vegetable fiber